Cross-border banking and business cycles in asymmetric currency unions - Lena Dräger; Christian R. Proa\~no (Bamberg University, Bamberg Economic Research Group (BERG), 2015)
Against the background of the emergence of macroeconomic imbalances within the European Monetary Union (EMU), we investigate in this paper the macroeconomic consequences of cross-border banking in monetary unions such as the euro area. For this purpose, we incorporate in an otherwise standard two-region monetary union DSGE model a global banking sector along the lines of Gerali et al. (2010), accounting for borrowing constraints of entrepreneurs and an internal constraint on the bank's leverage ratio. We illustrate in particular how rule-of-thumb lending standards based on the macroeconomic performance of the dominating region within the monetary union can translate into destabilizing spill-over effects into the other region, resulting in an overall higher macroeconomic volatility. Thereby, we demonstrate a channel through which the financial sector may have exacerbated the emergence of macroeconomic imbalances within the EMU. This effect may be partly mitigated if the central bank reacts to loan rate spreads, at least relative to the case with constant lending standards.
Keywords: F41; F34; E52; 330; cross-border banking; euro area; monetary unions; DSGE; monetary policy